2014
DOI: 10.1002/arp.1471
|View full text |Cite
|
Sign up to set email alerts
|

The Ancient Roman Aqueduct of Karales (Cagliari, Sardinia, Italy): Applicability of Geophysics Methods to Finding the Underground Remains

Abstract: Detection of the buried antique Roman aqueduct, which supplied fresh water to the ancient town of Karales (Cagliari, Italy), is not a trivial problem because of the small size of its cross section, its depth (about 10 m), and of the presence of shallow conductive layers. In order to determine the best geophysical method to use in the research of the conduit, a test was carried out over a well-known section of the underground aqueduct in its extra-urban part. Taking into account the geological features of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Identification of the underground stretches of these hydraulic works can be extremely difficult if direct access is not possible (due to closure or destruction of the shafts, and to falls within the structure). In the last years several authors have used different geophysical techniques to explore for and map these features, with particular regard to ground‐penetrating radar (GPR) (Bavusi et al ., ; Chaminé et al ., ; Galli et al ., ; Leucci, ; Leucci et al ., ; Leucci and De Giorgi, ; Nuzzo et al ., ; Sammarco et al ., ; Trogu et al ., ). However, the GPR literature is for the most part lacking models for what complex void spaces of various geometries look like in reflection profiles and other images, so these studies are still in their infancy (cf.…”
Section: Introductionmentioning
confidence: 97%
“…Identification of the underground stretches of these hydraulic works can be extremely difficult if direct access is not possible (due to closure or destruction of the shafts, and to falls within the structure). In the last years several authors have used different geophysical techniques to explore for and map these features, with particular regard to ground‐penetrating radar (GPR) (Bavusi et al ., ; Chaminé et al ., ; Galli et al ., ; Leucci, ; Leucci et al ., ; Leucci and De Giorgi, ; Nuzzo et al ., ; Sammarco et al ., ; Trogu et al ., ). However, the GPR literature is for the most part lacking models for what complex void spaces of various geometries look like in reflection profiles and other images, so these studies are still in their infancy (cf.…”
Section: Introductionmentioning
confidence: 97%
“…Comparing the two data sets may highlight less distinctive anomalies that could have otherwise been overlooked. The value of using multiple surveying techniques has been exemplified in multiple studies including those by Creighton and Fry (2016), Halgedahl et al (2009), Putiška et al (2014), Trogu et al (2014) and Zheng et al (2013).…”
Section: Introductionmentioning
confidence: 99%
“…Electrical resistivity prospection specifically proved to be an effective method to characterize the subsoil and materials in various fields of study, such as applied geology [2][3][4], hydrogeology [5,6], engineering [7][8][9], environmental sciences [10,11], and agriculture [12][13][14]. This method is widely used for archaeological surveys: many past research has shown that the variations of electrical resistivity are often related to walls, floorings, paving and burials [15][16][17][18][19][20][21][22]. These structures are generally characterized by different electrical properties compared to the geological layers that, over time, have buried them.…”
Section: Introductionmentioning
confidence: 99%